Dietary Proteins, Brown Fat, and Adiposity - Madsen, Lise; Myrmel, Lene Secher; Fjære, Even; Øyen, Jannike; Kristiansen, Karsten (Frontiers in Physiology, 2018)
High protein diets have become popular for body weight maintenance and weight loss despite controversies regarding efficacy and safety. Although both weight gain and weight loss are determined by energy consumption and expenditure, data from rodent trials consistently demonstrate that the protein:carbohydrate ratio in high fat diets strongly influences body and fat mass gain per calorie eaten. Here, we review data from rodent trials examining how high protein diets may modulate energy metabolism and the mechanisms by which energy may be dissipated. We discuss the possible role of activating brown and so-called beige/BRITE adipocytes including non-canonical UCP1-independent thermogenesis and futile cycles, where two opposing metabolic pathways are operating simultaneously. We further review data on how the gut microbiota may affect energy expenditure. Results from human and rodent trials demonstrate that human trials are less consistent than rodent trials, where casein is used almost exclusively as the protein source. The lack of consistency in results from human trials may relate to the specific design of human trials, the possible distinct impact of different protein sources, and/or the differences in the efficiency of high protein diets to attenuate obesity development in lean subjects vs. promoting weight loss in obese subjects.